Structure–Reactivity Relationships of Anomeric Amide Reagents in Nitrogen Deletion - Driscoll, Julia L.; Morales, Megan; Obertone, Carys E.; Park, Bumsu; Miguélez, Rubén; Levin, Mark D. (Synthesis, 2025)
N-(benzyloxy)-N-(pivaloyloxy)benzamides, a class of anomeric amide reagents, have enabled nitrogen deletion of secondary amines as well as deamination and deaminative functionalization of primary amines in a single step. While the application of these reagents has been expanding, current use is limited by the substrate limitations of existing anomeric amides. This report details the design and synthesis of novel anomeric amide derivatives with improved reaction kinetics, one of which demonstrates improved deletion yields in some instances. These studies shed light on the stereoelectronic effects governing the reactivity of anomeric amides within the context of nitrogen-deletion reactions.
Keywords: Skeletal editing; Stereo-electronic trends; Computational modeling; Atom deletion; Anomeric amide